A traffic noise model for road intersections in the city of Cartagena de Indias, Colombia. (August 2016) - Quiñones-Bolaños, Edgar Eduardo; Bustillo-Lecompte, Ciro Fernando; Mehrvar, Mehrab
Highlights: Motorcycles are an important source of noise in the city of Cartagena, Colombia. Motorcycles were included in the model as an additional vehicle category. Noise maps and a roadway noise model were developed for the city of Cartagena. Over 62% of road intersections in Cartagena do not comply with noise emission standards. The proposed model is able to predict equivalent roadway noise levels in Cartagena. Abstract: Road traffic noise models are fundamental tools for designing and implementing appropriate prevention plans to minimize and control noise levels in urban areas. The objective of this study is to develop a traffic noise model to simulate the average equivalent sound pressure level at road intersections based on traffic flow and site characteristics, in the city of Cartagena de Indias (Cartagena), Colombia. Motorcycles are included as an additional vehicle category since they represent more than 30% of the total traffic flow and a distinctive source of noise that needs to be characterized. Noise measurements are collected using a sound level meter Type II. The data analysis leads to the development of noise maps and a general mathematical model for the city of Cartagena, Colombia, which correlates the sound levels as a function of vehicle flow within road intersections. The highest noise levels were 79.7 dB(A) for the road intersection María Auxiliadora during the week (business days) and 77.7 dB(A) for the road intersection India Catalina during weekends (non-business days). Although traffic and noise are naturally related, the intersections with higher vehicle flow did not have the highest noise levels. The roadway noise for these intersections in the city of Cartagena exceeds current limit standards. The roadway noise model is able to satisfactorily predict noise emissions for road intersections in the city of Cartagena, Colombia.